PENGEMBANGAN KURIKULUM MUATAN LOKAL DALAM KONTEKS PENDIDIKAN ISLAM DI MADRASAH - Nasir, Muhammad (Hunafa: Jurnal Studia Islamika, 2013)
Abstract. One of the elements that must be preserved and maintained through education is values, traditions, culture, skills and concepts that apply to the public. In recent years, the government rolled out changes to the curriculum by adding local content subjects. Learning through local content, students were be expected to not only have academic knowledge in the form of global knowledge, but also have a concern for the values of the their surrounding socio-cultural. Conceptually, local content-based curriculum consists of two forms. The first form is attached to all subjects, and the two form a separate activity that has nothing to do with the subject. This paper, trying to explore how the model and the implementation of local content-based curriculum in Madrasah.Kata Kunci: Â Â Kurikulum, Muatan Lokal, Madrasah